Predictive Value of VEGF-C and D Combined with Ultrasound Pathological Features for Nonsentinel Lymph Node Metastasis in SLN-Positive Early-Stage Breast Cancer - Jianzhong Chen; Weifeng Li; Xinyuan Tang; Zhibin Wang; Liang Xu; Qiuming Liu (Clinical and Experimental Obstetrics & Gynecology)
Background: To explore the predictive value of vascular endothelial growth factor (VEGF)-C and D combined with ultrasonic pathological features for nonsentinel lymph node (NSLN) metastasis in positive sentinel lymph nodes (SLNs) early-stage breast cancer. Methods: To review the clinical data of 170 SLN-positive early breast cancer patients. We examined VEGF-C and D positive expression in cancerous and paraneoplastic tissues and counted ultrasound and pathological features. Results: The rate of VEGF-C and D positivity in cancer tissues was higher than that in paracancerous tissues (p < 0.05). The rates of VEGF-C and D positivity in the cancer tissues with vascular infiltration, number of SLN positives >2, proportion of SLN positives >0.5, burr sign on ultrasound, and NSLN metastasis were higher than those of patients without vascular infiltration, number of SLN positives ≤2, proportion of SLN positives ≤0.5, no burr sign, and no NSLN metastasis, respectively (p < 0.05). The results also showed that the presence of vascular infiltration and burr sign, a high number of SLN positivity, the percentage of SLN positivity >0.5, VEGF-C and D positivity were all NSLN metastasis independent risk factors for metastasis (p < 0.05). Receiver operating characteristic (ROC) curve analysis showed that the area under the ROC curve (AUC) for VEGF-C and D combined with ultrasound and pathological features to predict NSLN metastasis was the highest. Conclusions: The ultrasound and pathological features of SLN-positive early breast cancer patients, such as vascular infiltration, VEGF-C and D positivity, were all independent risk factors for NSLN metastasis, and VEGF-C and D combined with ultrasound and pathological features had high predictive efficacy for NSLN metastasis. It provides reliable indicators to screen for NSLN metastasis in a high-risk group from SLN-positive patients with early-stage breast cancer.